(untitled) - Nest, Dean G. Van (Ann Arbor, Mich., 1987)
This product is not a traditionally bound book. Many ProQuest UMI products are black-and-white reproductions of original publications produced through the Books On Demand ® program. Alternately, this product may be a photocopy of a dissertation or it may be a collection reproduced on microfiche or microfilm if it is intended for library purchase.
Keywords: New products,New products; Management